2022
DOI: 10.3390/horticulturae8020089
|View full text |Cite
|
Sign up to set email alerts
|

Delay of 1-MCP Treatment on Post-Harvest Quality of ‘Bosc Kobak’ Pear

Abstract: Information about 1-MCP application time on pears is crucial to optimize the schedule of treatment in commercial practice. In the present work, the effect of a 3, 5 and 7 d delay of 1-MCP treatment after harvest on ‘Bosc Kobak’ pears was investigated, with an emphasis on shelf life. Fruit was treated with 1-MCP (625 ppm) on the 3rd, 5th and 7th d after harvest for 24 h and then kept at 20 °C for 14 d or stored at 1 °C in normal atmosphere for 6 months. Ethylene, carbon dioxide production, flesh firmness, solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…Previous reports showed that fruit obtained from plants with a silenced EFE/ACO gene showed increased storage life in apples (Dandekari et al., 2004). In addition, inhibition of ethylene production or singling transduction resulted in increased postharvest quality in pears (Nguyen et al., 2022) and peaches (Liguori et al., 2004), as well as in other horticultural plants, such as Dianthus caryophyllus L (Xu et al., 2021) and chrysanthemum (Narumi et al., 2005). Further research to verify the putative genes that are linked to the postharvest storage by engineered transgenes or genetic research shall be conducted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports showed that fruit obtained from plants with a silenced EFE/ACO gene showed increased storage life in apples (Dandekari et al., 2004). In addition, inhibition of ethylene production or singling transduction resulted in increased postharvest quality in pears (Nguyen et al., 2022) and peaches (Liguori et al., 2004), as well as in other horticultural plants, such as Dianthus caryophyllus L (Xu et al., 2021) and chrysanthemum (Narumi et al., 2005). Further research to verify the putative genes that are linked to the postharvest storage by engineered transgenes or genetic research shall be conducted.…”
Section: Resultsmentioning
confidence: 99%
“…Results can be visualized by heat map, volcano map or data table (b, Step 4), the cross-species analysis can be performed by one click (b, Step 5) and the GO/ KEGG enrichment analysis can be further conducted (Figure 3b, Step 6). pears (Nguyen et al, 2022) and peaches (Liguori et al, 2004), as well as in other horticultural plants, such as Dianthus caryophyllus L (Xu et al, 2021) and chrysanthemum (Narumi et al, 2005). Further research to verify the putative genes that are linked to the postharvest storage by engineered transgenes or genetic research shall be conducted.…”
Section: Identify Key Genes Contributing To Postharvest Storage By In...mentioning
confidence: 99%
“…Furthermore, the treatment did have a positive effect on all other sample groups (turning, pink, light red and red tomatoes), which could be significantly observed after 1 week of storage time. It could be explained by the decreased ripening speed via blocking ethylene receptors and inhibiting its hormonal action by 1-MCP [ 2 , 3 , 4 ]. In general, the treatment was effective with different impacts for the sample groups.…”
Section: Discussionmentioning
confidence: 99%
“…The application of 1-methylcyclopropene (1-MCP) successfully controls the ripening of fruits and vegetables after harvest by inhibiting the negative effects of ethylene. There have been many reports about the role of 1-MCP in delaying the ripening and retaining the texture, taste and appearance of fruits and vegetables [ 2 , 3 , 4 ]. The 1-MCP treatment was shown to significantly delay the ripening of tomato [ 5 ]; however, the level of efficacy depends on the physiological stages of tomato [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%